2008
DOI: 10.1016/j.sbi.2008.04.004
|View full text |Cite
|
Sign up to set email alerts
|

RNA dynamics: it is about time

Abstract: SummaryMany recently discovered RNA functions rely on highly complex multi-step conformational transitions that occur in response to an array of cellular signals. These dynamics accompany and guide, for example, RNA co-transcriptional folding, ligand sensing and signaling, site-specific catalysis in ribozymes, and the hierarchically ordered assembly of ribonucleoproteins. RNA dynamics are encoded by both the inherent properties of RNA structure, spanning many motional modes with a large range of amplitudes and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
305
0

Year Published

2010
2010
2014
2014

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 301 publications
(309 citation statements)
references
References 50 publications
4
305
0
Order By: Relevance
“…It ranges from 200 nucleotides per second (nt/sec) in phages, to 20-80 nt/sec in bacteria and 10-20 nt/ sec for human polymerase II (Pan and Sosnick 2006). On the other hand, RNA folding is known to occur on a wide range of time scales; some RNAs fold in 10-100 msec (Al-Hashimi and Walter 2008), whereas kinetically trapped conformations can persist for minutes or hours (Sosnick and Pan 2003;Thirumalai and Hyeon 2005;Al-Hashimi and Walter 2008). Experiments in the early 1980s have shown that RNA structure formation can happen during transcription (Boyle et al 1980;Kramer and Mills 1981), i.e., cotranscriptionally, and that folding in vivo can happen on the same timescale as RNA synthesis (Brehm and Cech 1983).…”
Section: Transcription Transcription Speed and Variations Thereofmentioning
confidence: 99%
“…It ranges from 200 nucleotides per second (nt/sec) in phages, to 20-80 nt/sec in bacteria and 10-20 nt/ sec for human polymerase II (Pan and Sosnick 2006). On the other hand, RNA folding is known to occur on a wide range of time scales; some RNAs fold in 10-100 msec (Al-Hashimi and Walter 2008), whereas kinetically trapped conformations can persist for minutes or hours (Sosnick and Pan 2003;Thirumalai and Hyeon 2005;Al-Hashimi and Walter 2008). Experiments in the early 1980s have shown that RNA structure formation can happen during transcription (Boyle et al 1980;Kramer and Mills 1981), i.e., cotranscriptionally, and that folding in vivo can happen on the same timescale as RNA synthesis (Brehm and Cech 1983).…”
Section: Transcription Transcription Speed and Variations Thereofmentioning
confidence: 99%
“…Techniques including NMR and EPR relaxation have been developed to incisively probe motions in the ensemble on different time scales, ranging from picoseconds to milliseconds (3,4). Nonetheless, such dynamic information represents an average of the dynamics of the molecules across the conformational ensemble.…”
Section: Helix-junction-helix | Saxsmentioning
confidence: 99%
“…These concepts all invoke conformational flexibility (sampling) in both enzyme and substrate, derived from their structural dynamics, or the sum of all thermally activated global and local motions. While quite well established for protein enzymes (Fersht 1999;Hammes-Schiffer and Benkovic 2006), the potentially intricate linkage between function and structural dynamics is still much more tenuous for RNA (Al-Hashimi and Walter 2008).…”
Section: Introductionmentioning
confidence: 99%